Majelis Ulama Daerah Istimewa Aceh : fungsi dan organisasinya : laporan hasil penelitian - Rofai, Mohammad (Pusat Latihan Penelitian Ilmu-Ilmu Sosial, Aceh, 1979)
Structure and role of the Majelis Ulama, regional council of Islamic religious notables, in Aceh Province; research report.